(untitled) (Al-Qamar, 2023)
Allah subjected all the Prophets to trials and made these trials a source of forgiveness and pride for them, elevation of ranks, and the achievement of closeness. The people who come later should learn from their righteous behavior. It is not necessary that the trials come only on a sinful servant, rather, Allah Almighty causes His close ones to undergo trials so that their faith becomes more mature and that they learn to be grateful in every situation. All the prophets were subjected to trials, but they all proved to be perfect believers. They did not complain to Allah Almighty and were not ungrateful, because they promised themselves to suffer in the pleasure of their Lord, but Whenever any pain came to them, they said, "Our Lord, You are our Creator and Lord, We and all our wealth is from you, If you take it back, there must be some wisdom or expediency on your part, so make us among your grateful servants. His humility and trust made them more honorable and closer to his Lord.